Critical Pedagogy in ELT Practices for Teachers’ Professional Development - Zahra, Wardah (Global Expert: Jurnal Bahasa dan Sastra, 2024)
Encouraging students to reflect critical perspective of the use of English that is beyond the status quo creates globally compatible life skills and self-confidence. Indonesia, a non-English-speaking country, has faced several issues through the relation between critical pedagogy and teachers’ professional development in ELT practices. It is proven that Indonesia has low competency score test in the aspect of English skills and proficiency level, pedagogic skills, subject knowledge, and general academic aptitude and. Therefore, the low level of human resources in education in Indonesia certainly gives unsatisfied outcomes to society’s quality and ability. Keywords: Critical Pedagogy, ELT Practices, Teachers’ Professional Development